How does Pancasila work to solve social problems? - Zudana, Ahmad Yanta Fairuz (Indonesian Journal of Pancasila and Global Constitutionalism, 2023)
This study discusses the relationship that Pancasila has with the way it is used to overcome social problems that exist in Indonesia. This study uses the literature review method which explains that researchers in working only use sources from other research materials. The results obtained from this study are that to overcome social problems in the form of poverty, it is necessary to apply the fifth principle of Pancasila that all Indonesian people have the right to get the same thing and there is equality both at the level of the economy, education, and health. Furthermore, for the problem of war, it can be overcome by reflecting the first precept that every society has the right to choose what it believes in so that usually in its teachings it does not allow war except in special situations such as upholding justice. In the further context, for LGBT, it is necessary to apply the second principle that every human being has manners so that these LGBT actors should be embraced so that they can return to normal and not discriminate.